Challenge of gender equity and human rights on the threshold of the twenty-first century (ECLAC SantiagoCL, 2000)
Seeks to review progress and challenges in two areas of analysis viz. gender equity : the basis for a fair and equitable society, and human rights and peace for Latin America and the Caribbean.
Bibliography: p. 61-66